Sustainable Building through Project Planning Process - Alias, Anuar; Mohd Isa, Nor Kalsum; Abdul Samad, Zulkiflee (European Journal of Sustainable Development, 2014)
Planning process has a significant impact on the ability of a construction project to success. This is the stage where the detailed directions are given which would affect the whole course of the project. The process is argued to be the most crucial stage which the principles of sustainability are integrated throughout the whole life of building. The purpose of this research was to investigate the Malaysian building project stakeholders’ perspectives on the most significant strategies to integrate sustainability principles into the whole life of building through the project planning process. From the review of available literatures, there are 21 strategies to integrate sustainability principles during a building project planning process have been unveiled. A total of 357 Malaysian project stakeholders who have been directly involved in sustainable building project and/or the stakeholders who are judged to be knowledgeable on the project were selected to be contributed for questionnaire survey. The collected data were analyzed using cronbach’s alpha measurement to assess their internal reliability, and frequency and descriptive analysis to measure the relative importance of the factors. The result shows that all the 21 strategies (the factors) to integrate sustainability during a project planning process were identified by the respondents to be very crucial to be implemented throughout the planning process of a sustainable building project in Malaysia. This paper offers ideas and recommendations on the sustainability integration strategies to be practiced throughout the project planning process towards delivering a successful sustainable building project. The concept is very useful to be a starting point for the development of a practical ‘Sustainability Integration Framework’ during the planning process of a sustainable building project in the future. Keywords: Sustainable Building Project; Construction Project; Project Planning Process